MORPHOMETRY OF THE STINGLESS BEES OF THE GENUS LEPIDOTRIGONA (HYMENOPTERA: APIDAE: MELIPONINI) INDICATES OCCURRENCE OF MORE THAN ONE SPECIES IN INDIA - VIRAKTAMATH, SHASHIDHAR; THANGJAM, ROJEET (The Bioscan, 2023)
As a precursor to understand the diversity of stingless bees of the genus Lepidotrigona we made an exhaustive study on the morphometry of 122 bees representing eight states of northeastern India. Bees from Manipur were larger measuring 4.31 mm in body length as against the body length of 4.70 mm in primary type of Lepidotrigona arcifera. The median ocellus was two times larger (0.15 to 0.16 mm in diameter) than the median ocellus of the primary type (0.08 mm). Bees from Arunachal Pradesh, Nagaland and Sikkim had longer and wider forewings (4.48 to 4.49 and 1.50 to 1.55 mm, respectively) but the forewings of the primary type measured 4.60 and 1.65 mm. Hind tibia and hind basitarsus were longer and wider (1.50 and 0.67 mm, respectively) in the bees from Nagaland than in the primary type of L. arcifera (1.43 and 0.62 mm, respectively). The ratios of different parts of the body differed in the bees from northeastern India and the primary type. Principal Component and Canonical Discriminant analysis resulted in formation of 5 and 4 clusters, respectively. In both the methods, some bees from Arunachal Pradesh, Sikkim and Tripura formed separate clusters while the bees from remaining states formed an overlapping cluster. Based on these results we conclude that Indian fauna of Lepidotrigona bees consists of 4 to 5 species of ventralis group including L. arcifera. Further detailed studies need to be focused on inclusion of both females and associated males in description of these species.